Healthcare Worker With Large Vessel Acute Ischemic Stroke Likely Related to Mild SARS-CoV-2 Infection. (January 2022) - Castillo-Pinto, Carlos; Lamotte, Guillaume; Mehta, Amit; Sonti, Rajiv; Di Maria, Gianluca; Ruiz, Daniel; Kumar, Princy N.; Stemer, Andrew B.; Denny, M. Carter
We report the case of a healthcare worker who presented with a large vessel acute ischemic stroke in setting of a mild SARS-CoV-2 infection and provide a review of the emerging literature on COVID-related stroke. A 43-year-old female presented with right-sided hemiparesis, aphasia and dysarthria. She had a nonproductive of cough for 1 week without fever, fatigue or dyspnea. A CT Head, CT angiography and CT perfusion imaging revealed a M1 segment occlusion of the left middle cerebral artery requiring transfer from a primary to a comprehensive stroke center. A nasopharyngeal swab confirmed SARS-CoV-2 infection prior to arrival at the accepting center. During the thrombectomy a 3 cm thrombus was removed. Thrombus was also evident in the 8 French short sheath during closure device placement so a hypercoagulable state was suspected. Stroke work-up revealed a glycosylated hemoglobin of 8.7%, elevation of inflammatory markers and an indeterminate level of lupus anticoagulant IgM. On discharge home, she had near complete neurological recovery. This case highlights suspected mechanisms of hypercoagulability in SARS-CoV-2 infection and the importance of optimizing stroke care systems during the COVID-19 pandemic.